2021
DOI: 10.1126/sciadv.abf0068
|View full text |Cite
|
Sign up to set email alerts
|

The source of the major solar energetic particle events from super active region 11944

Abstract: Shock waves associated with fast coronal mass ejections (CMEs) accelerate solar energetic particles (SEPs) in the long duration, gradual events that pose hazards to crewed spaceflight and near-Earth technological assets, but the source of the CME shock-accelerated plasma is still debated. Here, we use multi-messenger observations from the Heliophysics System Observatory to identify plasma confined at the footpoints of the hot, core loops of active region 11944 as the source of major gradual SEP events in Janua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 67 publications
(81 reference statements)
2
30
0
Order By: Relevance
“…Previous studies have tried to link these features to in situ measurements of the solar wind, and we are currently investigating their role in the production of solar energetic particles (SEPs). Plasma composition measurements are important for SEP connection studies (Brooks & Yardley 2021), and further work on this topic will be the focus of missions such as Solar Orbiter and Parker Solar Probe. In fact, Harra et al (2021) have already analysed a series of small type III bursts observed by Parker Solar Probe in order to identify the source of SEPs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies have tried to link these features to in situ measurements of the solar wind, and we are currently investigating their role in the production of solar energetic particles (SEPs). Plasma composition measurements are important for SEP connection studies (Brooks & Yardley 2021), and further work on this topic will be the focus of missions such as Solar Orbiter and Parker Solar Probe. In fact, Harra et al (2021) have already analysed a series of small type III bursts observed by Parker Solar Probe in order to identify the source of SEPs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The suitability of this method for measurements of the solar coronal magnetic field has been recently demonstrated by Chen et al (2021) through a forward modeling approach. This technique has also been successfully applied to solar extreme ultraviolet (EUV) spectral observations (e.g., Si et al 2020;Landi et al 2020Landi et al , 2021Brooks & Yardley 2021). The measured field strengths in solar ARs are often several hundred Gauss, which is consistent with the typical field strengths in the lower corona as derived from magnetic field extrapolations (Landi et al 2020) and magnetohydrodynamic (MHD) models (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 66%
“…More recently, Brooks & Yardley (2021) have identified the source region of the energetic particles during an eruption. Again, our model corroborates and explains those findings as it shows that the ICME can maintain a distinguished chemical composition during its motion in the interplanetary space with a limited mixing of the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopy usually provides important information about element abundances (e.g. Lee & Raymond 2012), and it has been used, for instance, to track the presence of solar energetic particles (SEP) in ICMEs (Brooks & Yardley 2021), but in situ measurements would represent the best solution for directly measuring the composition of solar mass transported by ICMEs close to Earth. Studying the chemical composition of ICME plasma allows one to trace back its origin on the different layers of the solar atmosphere, also taking advantage of the so-called first ionisation potential (FIP) effect (see recent review by Song & Yao 2020).…”
Section: Introductionmentioning
confidence: 99%